Art and imagination: A study in the philosophy of mind - Scruton, Roger (London Methuen & Co, 1974)
Roger Vernon Scruton (born 27 February 1944) is a conservative English philosopher, writer and composer. He is the author of over 30 books, including Art and Imagination (1974), Sexual Desire (1986), The Aesthetics of Music (1997), and A Political Philosophy: Arguments for Conservatism (2006). He has also written several novels and two operas. Scruton was a lecturer and professor of aesthetics at Birkbeck College, London, from 1971 to 1992. Since 1992 he has held part-time positions at Boston University, the American Enterprise Institute in Washington, D.C., and the University of St Andrews. In 1982 he helped found The Salisbury Review, a conservative political journal, which he edited for 18 years. He also founded the Claridge Press in 1987, and he sits on the editorial board of the British Journal of Aesthetics. Scruton is a member of the International Advisory Board of the Center for&